2004
DOI: 10.1097/01.hco.0000141267.26503.ed
|View full text |Cite
|
Sign up to set email alerts
|

Stent graft treatment for abdominal aortic aneurysm repair: recent developments in therapy

Abstract: This article describes the general principles of use for endovascular devices for the repair of abdominal aortic aneurysms. It details the features and results for the devices in current use, and highlights the recent developments in stent graft treatment of abdominal aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A few years later, an evolution of the Enovus was proposed for human application with the name of Ovation Endograft (Endologix, Irvine, CA, USA). After successful animal investigations [72], the platform was tested in clinical trials with positive feedback, which was a fundamental evolution in the use of polymers in the EVAR field. The endograft is based on a new concept design separating fixation from sealing-fixation activity is assured by a suprarenal stent and anchors (not different from traditional suprarenal EVAR devices), while sealing activity is based on inflatable O-rings filled with a low-viscosity, non-embolic, radiopaque fill polymer instead of traditional self-expanding stent grafts.…”
Section: The O-ring Evar Polymer-based Proximal Neck Sealing Device So-called Ovation Stent Graftmentioning
confidence: 99%
“…A few years later, an evolution of the Enovus was proposed for human application with the name of Ovation Endograft (Endologix, Irvine, CA, USA). After successful animal investigations [72], the platform was tested in clinical trials with positive feedback, which was a fundamental evolution in the use of polymers in the EVAR field. The endograft is based on a new concept design separating fixation from sealing-fixation activity is assured by a suprarenal stent and anchors (not different from traditional suprarenal EVAR devices), while sealing activity is based on inflatable O-rings filled with a low-viscosity, non-embolic, radiopaque fill polymer instead of traditional self-expanding stent grafts.…”
Section: The O-ring Evar Polymer-based Proximal Neck Sealing Device So-called Ovation Stent Graftmentioning
confidence: 99%
“…In addition, although mortality rates are reasonably low in uncomplicated cases (5%), higher rates are often associated in those with co-morbid diseases such as coronary artery disease and renal failure. 46 OSR may also result in significant harm to the patient, with myocardial infarction, respiratory and renal failure, and changes in functional status possibly occurring. 71,123 Finally, recovery rates are in the region of several months, resulting in a reduction in quality of life for the patients for up to 3 months post-operatively.…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9][10] Endovascular therapy is a minimally invasive technique that has been widely used to treat various vascular diseases, especially abdominal and thoracic aortic aneurysms. [11][12][13][14] Recently, several studies have reported the management of IVIs with endovascular techniques. 15,16 In this study, we aimed to evaluate the application of endovascular techniques including endograft placement, embolization and balloon compression in the treatment of different types of IVIs.…”
Section: Introductionmentioning
confidence: 99%